Evolutionary dynamics of transposable elements and satellite DNAs in polyploid Spartina species. (January 2021) - Giraud, Delphine; Lima, Oscar; Huteau, Virginie; Coriton, Olivier; Boutte, Julien; Kovarik, Ales; Leitch, Andrew R.; Leitch, Ilia J.; Aïnouche, Malika; Salmon, Armel
Highlights: First repeat annotations from high-throughput genome sequencing in polyploid Spartina . Repeat dynamics among Spartina species is correlated with phylogenetic relationships. Genome evolution is determined by divergence times rather than by ploidy levels. Repeat patterns of the tetraploid S. spartinae suggest relationships with hexaploids. Burst of novel 370pb-satellite DNA representing 6.89 % of the S. alterniflora genome. Abstract: Repeated sequences and polyploidy play a central role in plant genome dynamics. Here, we analyze the evolutionary dynamics of repeats in tetraploid and hexaploid Spartina species that diverged during the last 10 million years within the Chloridoideae, one of the poorest investigated grass lineages. From high-throughput genome sequencing, we annotated Spartina repeats and determined what sequence types account for the genome size variation among species. We examined whether differential genome size evolution correlated with ploidy levels and phylogenetic relationships. We also examined the tempo of repeat sequence dynamics associated with allopatric speciation over the last 3–6 million years between hexaploid species that diverged on the American and European Atlantic coasts and tetraploid species from North and South America. The tetraploid S. spartinae, whose phylogenetic placement has been debated, exhibits a similar repeat content as hexaploid species, suggesting common ancestry. Genome expansion or contraction resulting from repeat dynamics seems to be explained mostly by the contrasting divergence times between species, rather than by genome changes triggered by ploidy level change per se . One 370 bp satellite may be exhibiting 'meiotic drive' and driving chromosome evolution in S. alterniflora . Our results provide crucial insights for investigating the genetic and epigenetic consequences of such differential repeat dynamics on the ecology and distribution of the meso- and neopolyploid Spartina species.